2004
DOI: 10.1007/s10072-004-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

New daily persistent headache: clinical and serological characteristics in a retrospective study

Abstract: We present a retrospective clinical study of 18 cases of new daily persistent headache (NDPH), a rare chronic headache, included in the fourth chapter of the II IHS classification; the pathophysiology of NDPH is unknown but a link with viral infections (especially Epstein-Barr virus (EBV)) has been suggested. Comparing our series with the other two published until now, we did not find any particular difference, as regards to clinical aspects. However, our laboratory tests show a recent herpes simplex virus inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 7 publications
3
71
0
4
Order By: Relevance
“…Because of the report that many patients experience an antecedent flu-like illness, a postinfectious phenomenon has been postulated, 16 often attributed to Epstein-Barr virus 17 or other infections. 11 Our finding that NDPH patients can have their headache onset in a biphasic pattern during the beginning of spring and autumn could also impart a seasonal trigger, such as an infection, as a common inciting factor. However, though NDPH patients may have elevated CSF levels of a proinflammatory cytokine, tumor necrosis factor-␣, this does not seem related to having a history of an antecedent infection.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Because of the report that many patients experience an antecedent flu-like illness, a postinfectious phenomenon has been postulated, 16 often attributed to Epstein-Barr virus 17 or other infections. 11 Our finding that NDPH patients can have their headache onset in a biphasic pattern during the beginning of spring and autumn could also impart a seasonal trigger, such as an infection, as a common inciting factor. However, though NDPH patients may have elevated CSF levels of a proinflammatory cytokine, tumor necrosis factor-␣, this does not seem related to having a history of an antecedent infection.…”
Section: Discussionmentioning
confidence: 80%
“…In an Italian series of 18 patients, 66% remitted within 24 months. 11 In our series, we did not follow all patients over a 24-month period, but over half of the patients with the persisting subform had continuing daily headache for 24 months or longer. Of the patients who remitted, 63.6% did so within 24 months.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is more common in females, with the female/male ratio in adults at 2.5:1 [5] and in children and adolescents at 1.8:1 [4•]. It has an earlier age of onset in women (ages [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] than in men (ages 26-45) [5]. One study of 680 pediatric headache clinic patients reported 189 (28%) with tension-type headache, 34 of whom met NDPH criteria [7].…”
Section: Epidemiologymentioning
confidence: 99%
“…1 Onset of chronic tensiontype headache (CTTH) and chronic migraine (CM) compared with that of new daily persistent headache (NDPH). CTTH and CM both have a gradual increase in frequency (A), whereas NDPH has an abrupt onset (B) cytomegalovirus, Salmonella, adenovirus, Toxoplasma, and herpes zoster [1,20,24]. Given the variety of infectious associations, it has been postulated that the nonspecific inflammatory response initiated by the infection, rather than the infectious agent itself, may be the trigger [6].…”
Section: Pathophysiologymentioning
confidence: 99%